2023
DOI: 10.3389/fnagi.2023.1241237
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of cerebrospinal fluid space between probable normal pressure hydrocephalus and Alzheimer’s disease

Hongliang Li,
Chunyan Liu,
Hong Tai
et al.

Abstract: IntroductionIdiopathic normal pressure hydrocephalus (INPH) is a potentially reversible syndrome characterized by complex symptoms, difficulty in diagnosis and a lack of detailed clinical description, and it is difficult to distinguish from Alzheimer’s disease (AD). The objective of this study was to design a method for measuring the actual amount of hydrocephalus in patients with INPH and to evaluate INPH.MethodsAll subjects underwent a 3D T1-weighted MRI. Statistical parametric mapping 12 was used for prepro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…In 1965, Hakim and Adams proposed the hypothesis that iNPH was caused by an increase in CSF-volume and compensatory ventricular enlargement ( Hakim and Adams, 1965 ). Some research results have shown that iNPH patients have significantly reduced white matter volume, while cerebrospinal fluid volume, cerebrospinal fluid ratio, and total intracranial volume are significantly increased, supporting this hypothesis ( Li et al, 2023 ). Currently, the main causes of CSF-volume increase are believed to be CSF absorption disorders and increased CSF production ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 82%
“…In 1965, Hakim and Adams proposed the hypothesis that iNPH was caused by an increase in CSF-volume and compensatory ventricular enlargement ( Hakim and Adams, 1965 ). Some research results have shown that iNPH patients have significantly reduced white matter volume, while cerebrospinal fluid volume, cerebrospinal fluid ratio, and total intracranial volume are significantly increased, supporting this hypothesis ( Li et al, 2023 ). Currently, the main causes of CSF-volume increase are believed to be CSF absorption disorders and increased CSF production ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 82%
“…Yamada et al’s studies on indices characterizing CSF spaces for the optimal distinction of probable NPH from healthy controls ( 29 ), AD, and NPH-and-AD cohorts on T2-MRI ( 38 ) were also based on semi-quantitative approaches relying on automatic segmentation of brain tissue. In a recent study of CSF distribution, the normalized WM and CSF volumes derived using VBM, along with the CA were shown to provide improved distinction between probable NPH and AD using MRI sequences when compared to the CA alone ( 77 ).…”
Section: Computational Methods For the Detection Of Nph And Its Diffe...mentioning
confidence: 99%